Derisking the Cu-mediated (18)F-fluorination of heterocyclic positron emission tomography radioligands - Taylor, N; Emer, E; Preshlock, S; Schedler, M; Tredwell, M; Verhoog, S; Mercier, J; Genicot, C; Gouverneur, V (American Chemical Society, 2017)
Molecules labeled with fluorine-18 ((18)F) are used in positron emission tomography to visualize, characterize and measure biological processes in the body. Despite recent advances in the incorporation of (18)F onto arenes, the development of general and efficient approaches to label radioligands necessary for drug discovery programs remains a significant task. This full account describes a derisking approach toward the radiosynthesis of heterocyclic positron emission tomography (PET) radioligands using the copper-mediated (18)F-fluorination of aryl boron reagents with (18)F-fluoride as a model reaction. This approach is based on a study examining how the presence of heterocycles commonly used in drug development affects the efficiency of (18)F-fluorination for a representative aryl boron reagent, and on the labeling of more than 50 (hetero)aryl boronic esters. This set of data allows for the application of this derisking strategy to the successful radiosynthesis of seven structurally complex pharmaceutically relevant heterocycle-containing molecules.